PENGEMBANGAN BAHAN AJAR ALJABAR LINEAR ELEMENTER BERDASARKAN KEMAMPUAN KONEKSI MATEMATIS - FITRIAWAN, DONA (Universitas Tanjungpura, 2020)
The purpose of this study is to develop: 1. elementary linear algebra teaching materials based on mathematical connection skills; 2. syllabus and lecture plan; 3. test mathematical connection skills. This type of research is a research and development approach whose research design consists of four stages, namely defining, planning, developing, and dissiminating. Data analysis techniques in this study describe narratively the steps in developing teaching materials. Based on the results of the analysis of the data obtained that: 1) the stages of developing teaching materials starting from the stages of defining, designing, until the first stage of development, namely expert validation. From this stage of development a revised elementary linear algebra teaching material has been produced based on input from three validators. Teaching materials compiled consist of four materials, namely systems of linear equations, matrices, inverses, and matrix determinants; 2) based on the opinions of three experts, elementary linear algebra teaching materials that have been compiled are classified as valid and good in terms of accuracy of contents, digestibility, use of language, so that they can be used to develop mathematical connection skills.AbstrakTujuan dari penelitian ini adalah untuk mengembangkan: 1. bahan ajar aljabar linier dasar berdasarkan keterampilan koneksi matematika; 2. silabus dan rencana kuliah; 3. menguji keterampilan koneksi matematika. Jenis penelitian ini adalah pendekatan penelitian dan pengembangan yang desain penelitiannya terdiri dari empat tahap, yaitu mendefinisikan, merencanakan, mengembangkan, dan menyebarluaskan. Teknik analisis data dalam penelitian ini menggambarkan secara naratif langkah-langkah dalam mengembangkan bahan ajar. Berdasarkan hasil analisis data diperoleh bahwa: 1) tahap pengembangan bahan ajar mulai dari tahap pendefinisian, perancangan, hingga tahap pertama pengembangan, yaitu validasi ahli. Dari tahap pengembangan ini bahan ajar aljabar linier revisi telah dihasilkan berdasarkan masukan dari tiga validator. Bahan ajar yang disusun terdiri dari empat bahan, yaitu sistem persamaan linear, matriks, invers, dan determinan matriks; 2) berdasarkan pendapat tiga ahli, bahan ajar aljabar linier dasar yang telah disusun diklasifikasikan sebagai valid dan baik dalam hal keakuratan isi, kecernaan, penggunaan bahasa, sehingga dapat digunakan untuk mengembangkan keterampilan koneksi matematis.Kata Kunci: bahan ajar, kemampuan koneksi matematis